APLIKASI SOFTWARE CABRI DALAM PEMBELAJARAN MATEMATIKA - Siregar, Rahma Hayati (IAIN PADANGSIDIMPUAN, 2016)
For breaking the problem abstract in mathematics be needed instrument aid about studing. For example, if we want to introduce triangle that in can be beginning from carton or paper continue with palm leaf rib or new cable than triangle picture more abstract. But using this aid tools must consider principle development aid tool studied. In order that this aid suer help student to study suit prospects. One of them aid instrument development speedy this time is multimedia (computer). Looking about this problem, the solution suit is attend multimedia as aid instrument studing. Choise multimedia enough various. For geometry is two dimension chose CABRI.